Fishermen Empowerment Strategies Through The Fishermen Group Program By The Takalar District Marine And Fisheries Office - Hamid, Hendrawati (Journal of Management, 2023)
The goal of this study is to examine the Takalar Regency Fisheries Service's strategies for empowering fishermen through the fishermen group program, in the hope that the welfare and independence of fishermen will improve, thereby influencing regional economic growth. A descriptive qualitative research methodology was adopted. Informants are selected using purposive sampling. Data were gathered through in-depth interviews with informants including the Head of the Department, the Head of the relevant Division at the Department of Maritime Affairs and Fisheries, Fisheries Extension Officers, and fishermen leaders. In addition, observations and a literature review were done. The SWOT technique was used to analyze the data. The results demonstrated that the Fisheries Service's plan followed the correct flow and adhered to the appropriate SOPs. Internal and external elements are equally influential in the implementation of the fisherman group program, where external factors have a good chance, but must also be balanced with the ability to manage and protect the sea's potential from irresponsible parties. Internal variables have a negative impact on the program if the service apparatus fails to carry out a decent work ethic in accordance with their individual obligations.